2005
DOI: 10.1002/hep.20877
|View full text |Cite
|
Sign up to set email alerts
|

Steatohepatitis Induced by Intragastric Overfeeding in Mice *

Abstract: Nonalcoholic steatohepatitis is prevalent among obese individuals with excessive caloric intake, insulin resistance, and type II diabetes. However, no animal models exist that recapitulate this important association. This study produced and characterized steatohepatitis (SH) caused by intragastric overfeeding in mice. C57BL/6, tumor necrosis factor (TNF) type I receptor-deficient, and genetically matched wild type mice were fed via an implanted gastrostomy tube a high-fat diet for 9 weeks in the increasing amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
180
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(189 citation statements)
references
References 52 publications
(59 reference statements)
6
180
3
Order By: Relevance
“…De novo fatty acid synthesis is regulated by the ER stress-associated transcription factor nSREBP-1c (Deng et al, 2005), whereas phosphorylation and activation of hepatic AMPK suppress the expression of hepatic SREBP-1c and its target lipogenic enzymes (Zhou et al, 2001). Previously, we found that SREBP-1c and its downstream-regulated genes FAS, ACC, and SCD were activated in ethanol-fed micropigs, correlating with reduced levels of the SAM to SAH ratio (Esfandiari et al, 2005).…”
Section: Discussionmentioning
confidence: 90%
“…De novo fatty acid synthesis is regulated by the ER stress-associated transcription factor nSREBP-1c (Deng et al, 2005), whereas phosphorylation and activation of hepatic AMPK suppress the expression of hepatic SREBP-1c and its target lipogenic enzymes (Zhou et al, 2001). Previously, we found that SREBP-1c and its downstream-regulated genes FAS, ACC, and SCD were activated in ethanol-fed micropigs, correlating with reduced levels of the SAM to SAH ratio (Esfandiari et al, 2005).…”
Section: Discussionmentioning
confidence: 90%
“…Since no changes in transcriptome expression of proinflammatory or profibrotic cytokines (e.g., TNF-a, IL-1b, IL-18, TGF-b, and others), classically thought to mediate liver injury including fibrosis, were identified in the HCD-fed mouse liver, it seems that these classic proinflammatory cytokines, at least those secreted in the liver, may not be critically involved in the early aspects of this disease. The lack of TNF-a participation in dietary-induced NASH was recently suggested by Deng et al [7], who demonstrated that knocking out the TNF-a receptor 1 does not prevent NASH induced by forcefeeding a fat-enriched diet. Similar studies by Dela Pena et al [26] showed that TNFR1 knockout mice still develop hepatic steatosis when fed a methionine-restricted, cholinedeficient diet.…”
Section: Discussionmentioning
confidence: 93%
“…Experimental models based on voluntary food intake have been developed to induce hepatic steatosis in laboratory animals [2][3][4][5][6][7][8]. The nutritional models using complete diets resemble the human condition in that they contain amounts of lipids or carbohydrates that exceed the energy needs of the body.…”
Section: Introductionmentioning
confidence: 99%
“…Although several animal models have been proposed, many of them are based on genetic defects or special diet-induced factors, so it is difficult to determine the exact disease process of NASH on the basis of metabolic syndrome alone. [7][8][9] We previously described a murine model of NASH induced by neonatal subcutaneous injection of monosodium glutamate (MSG), which includes the clinical manifestations of central obesity, diabetes, hyperlipidemia, and ultimately, liver inflammation, fibrosis, and liver tumor, similar to the manifestations that are present in the human liver. 10,11 Tsumura Suzuki obese diabetes (TSOD) mice are novel polygenic models of spontaneous type-2 diabetes mellitus that develop moderate degrees of obesity, especially apparent in animals more than 11 weeks of age.…”
mentioning
confidence: 99%